Drogue et crime : l’impact du commerce de drogues sur le tissu urbain - Rengert, George (Criminologie, 1994)
The problem addressed in this analysis is whether « routine activities » of drug dependent criminals are associated with the spatial concentration of crime committed by these criminals. This problem is tested in a series of analyses including an investigation of the spatial pattern of the residential burglaries committed by drug dependent burglars using W.A.V. Clark's spatial choice housing search models. While Clark used the home and work place as nodes in the housing search, we use the home and drug market place as nodes in the criminal search of drug addicts. If the addict supports his or her habit with property crime, these nodes are expected to be a focal point for criminal activity in a distance minimizing scenario. The data indicate that the spatial concentration of property crime about drug market places means that a « crime containment » policy practiced by many police agencies is doomed to failure. Property criminals will continue to probe outward from a containment area which encompasses a drug market place. In fact, drug dependent property criminals may act as a vanguard for spatially expanding drug markets. Drug sellers and drug dependent property criminals seem to operate in a symbiotic relationship.